भारतीय भाषा ज्योति - तेलुगु (भाग-1) - Srinivasacharya, K.; Nagaraj, P. (My University, 2000)
This book is Bharatiya Bhasha Jyoti consisting of 24 Units on learing.
Bharatiya Bhasha Jyothi - Telugu – Part I
Keywords: Telugu